Athlete-opponent interdependency alters pacing and information-seeking behavior - Konings, M. J.; Foulsham, T.; Micklewright, D.; Hettinga, F. J. (Medicine & Science in Sports & Exercise, 2020)
Purpose The influence of interdependency between competitors on pacing decision-making and information-seeking behavior has been explored. This has been done by only altering instructions, and thereby action possibilities, while controlling environment (i.e., competitor behavior) and exercise task. Methods Twelve participants performed a 4-km time trial on a Velotron cycle ergometer in a randomized, counterbalanced order alone with no virtual opponent (NO), against a virtual opponent with no restrictions (low athlete-opponent interdependency [OP-IND]), or against a virtual opponent who the participant was permitted to overtake only once during the trial (high athlete-opponent interdependency [OP-DEP]). Information-seeking behavior was evaluated using an SMI eye tracker. Differences in pacing, performance, and information-seeking behavior were examined using repeated-measures ANOVA (P < 0.05). Results Neither mean power output (NO, 298 ± 35 W; OP-IND, 297 ± 38 W; OP-DEP, 296 ± 37 W) nor finishing time (NO, 377.7 ± 17.4 s; OP-IND, 379.3 ± 19.5 s; OP-DEP, 378.5 ± 17.7 s) differed between experimental conditions. However, power output was lower in the first kilometer of OP-DEP compared with the other experimental conditions (NO, 332 ± 59 W; OP-IND, 325 ± 62 W; OP-DEP, 316 ± 58 W; both P < 0.05), and participants decided to wait longer before they overtook their opponent (OP-IND, 137 ± 130 s; OP-DEP, 255 ± 107 s; P = 0.040). Moreover, total fixation time spent on the avatar of the virtual opponent increased when participants were only allowed to overtake once (OP-IND, 23.3 ± 16.6 s; OP-DEP, 55.8 ± 32.7 s; P = 0.002). Conclusion A higher interdependency between athlete and opponent altered pacing behavior in terms of in-race adaptations based on opponent`s behavior, and it induced an increased attentional focus on the virtual opponent. Thus, in the context of exercise regulation, attentional cues are likely to be used in an adaptive way according to their availability and situational relevance, consistent with a decision-making framework based on the interdependence of perception and action.